Rereading Conrad - Schwarz, Daniel R. (University of Missouri Press, 2001)
"Rereading Conrad sheds new light on an author who has spoken to readers for over a century. Schwarz's essays take account of recent developments in theory and cultural studies, including postcolonial, feminist, gay, and ecological perspectives, and show how reading Conrad has changed in the face of the theoretical explosion that has occurred over the past two decades. Because for over three decades Schwarz has been an important figure in defining how we read Conrad and in studying modernism, including how we respond to the relationship between modern literature and modern art, scholars, teachers, and students will take great pleasure in this new collection of his work."--Jacket